Wong's essentials of pediatric nursing - Wong, Donna L.; Hockenberry-Eaton, Marilyn ;Wilson, David ;Winkelstein, Marilyn L. ;Schwartz, Patricia (St. Louis, Missouri : Mosby Elsevier, 2001)
This leading pediatric nursing textbook owes its success to scrupulous accuracy, current research, and a highly readable style. The new edition, packed with full color, many special features, and the most comprehensive package available, maintains the high standards established by previous editions. A new chapter on community-based nursing care of children has been added to address this increasingly important health care arena. The first part of the book on child development and health promotion lays the foundation for understanding later chapters on specific health problems - organized by age groups and body systems. The nursing process is used to format major diseases, disorders, and conditions.
Unit 1. Children, Their Families, and the Nurse -- Unit 2. Assessment of the Child and Family -- Unit 3. The Newborn. 8. Health Promotion of the Newborn and Family -- Unit 4. Infancy -- Unit 5. Early Childhood -- Unit 6. Middle Childhood and Adolescence -- Unit 7. The Child and Family with Special Needs -- Unit 8. Impact of Hospitalization on the Child and Family -- Unit 9. The Child with Problems Related to the Transfer of Oxygen and Nutrients -- Unit 10. The Child with Problems Related to the Production and Circulation of Blood -- Unit 11. The Child with a Disturbance of Regulatory Mechanisms -- Unit 12. The Child with a Problem That Interferes with Physical Mobility
Includes index.
Keywords: PEDIATRIC NURSING